Diversidade e descolonização do currículo do ensino superior: diálogos Brasil e Estados Unidos - Santos, Fernanda Vieira da Silva (2018)
This paper is a result of a research entitled "Knowledge, research and innovation in teacher education for ethnic-racial development in higher education: questionings and contributions of the ethnic-racial and cultural matrices of African and Afro-descendant knowledge", from the Center for Studies Afro-Brazilians (NEAB) of the Federal University of São Carlos (UFSCar), in which this project is the result of the Academic Development Program Abdias Nascimento, for the grant of the Coordenação de Aperfeiçoamento do Pessoal de Nível Superior (CAPES). Thus, the study is divided into three sections: First, a Abdias Nascimento’s biography, second a review literature from data bases: Institute of Educational Sciences (ERIC) and Electronic Scientific Library (SCIELO), and the history of Higher Education in Brazil and United States ; Finishing with reflexions about higher education and race relations. There are also the Appendices on the implementation of the Academic Development Program Abdias Nascimento, with a perspective on the dissemination of race relations during this internship. Throughout the paper it was presented historical syntheses on the challenges of the black population to get access to Higher Education